THE CAUSING FACTORS OF SOCIAL PROBLEMS OF THE LEFT-HANDED CHARACTER IN NANCY SPRINGER’S NOVEL ENOLA HOLMES - Wahyu Utama Putra; Muhammad Ali Pawiro; Ely Ezir (JOURNAL OF LANGUAGE, 2023)
The aim of this research is to reveal the causing factors of social problems in Springer’s novel Enola Holmes, referring to the issues or challenges that affect society and its members, hindering their overall well-being and quality of life. These problems arise due to various factors, including economic, political, cultural, and structural issues. Descriptive method is used in analyzing the data as a comprehensive summarization in everyday terms of specific events experienced by individuals and groups. The analysis holistically is supported by the theory of Marxism proposed by Karl Marx and supported by Friedrich Engels, Stanley Coren, and others related to the analysis. Research on the causing factors of social problems of left-handed character is significant for advancing equality, raising awareness, informing policies, and enhancing the well-being and quality of life for left-handed people. By addressing the unique challenges they face, society can strive to create an inclusive environment that values and supports the diverse needs of all individuals, regardless of their handedness. It is found that there are various causing factors of social problems delving into various domains, such as racism and discrimination, men’s rules everything, and underestimated, that affect the character’s existence as a human and a woman.